Sistema de prevención de riesgos ergonómicos para los operadores de efluentes de la planta de aguas residuales de la empresa productora de gelatina prodegel s.a. de la ciudad de Ambato - Lozano Suárez, Edgar Vicente (2018)
The research work developed under the title "Ergonomic risk prevention system for effluent operators of the wastewater plant of the gelatin producing company PRODEGEL S.A. of the city of Ambato ", was executed through an analysis of the before and after working conditions to obtain an effective diagnosis on the genesis of the problem and establish the corresponding improvements to the problem. A diagnosis is established in the first instance that serves as a research baseline by identifying the risks through the risk matrix specifically for the ergonomic part, which identifies the unsafe actions and conditions of the job and subsequently the identification of risk factors with the criteria established in the MAPFRE guide for the quantitative assessment of the level of risk. An evaluation was applied to identify the presence or absence of symptomatology of musculoskeletal conditions through the Nordic Test and to identify the conditions before and after the implementation of the equipment and its use. This methodology was evaluated by means of a reliability test to obtain the Cronbach's Alpha coefficient. The research analyzed the different positions adopted by the operators during the development of the activity, which allowed carrying out the evaluations of the working conditions prior to the implementation of the improvements developed. The methodology used to evaluate the postural load and the dynamic physical load before and after the implementation of the prevention program was developed by means of the REBA and NTP 177 method, respectively, to establish the level of the present risk factor. It is concluded that the present work has a high impact since it has developed an ergonomic risk prevention program for effluent operators that has eliminated musculoskeletal symptoms preventing them from degenerating into musculoskeletal disorders limiting workers to the development of activity.